Comparative Analysis of Elementary Mathematics Textbooks on Geometry in Indonesia and the United States - Puspitaningrum, Rifky; Purnomo, Yoppy Wahyu (FKIP Universitas Lampung, 2025)
Comparative Analysis of Elementary Mathematics Textbooks on Geometry in Indonesia and the United States. Objectives: This study aims to describe a comparison between elementary mathematics textbooks from Indonesia and the United States, focusing on geometry content. The analysis covers mathematical content based on Van Hiele’s levels of geometric thinking and Gracins’ framework, including mathematical activities, task complexity levels, response formats, and contextual features. Methods: A qualitative approach was employed, using coding and content recording techniques on Indonesian mathematics textbooks (Matematika SD/MI) and the Go Math! series from the United States across all elementary grade levels. Horizontal and vertical analyses were conducted. Inter-rater reliability was tested using Fleiss’ Kappa via JASP software, yielding high agreement levels ranging from